2013
DOI: 10.6023/cjoc201302001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Disproportionation and Hydrolysis Reactions of 3-Amino-4-hydroxyaminoximinofurazan

Abstract: A novel energetic intermediate 3-amino-4-hydroxyaminoximinofurazan (DOAF) was synthesized from 3-amino-4amidoximinofurazan (DAOF) via diazotisation and oximation reactions with a total yield of 61.8%, and its structure was characterized by NMR, IR, MS and elemental analysis. The main factors for the oximation reaction were thoroughly studied, and the optimum reaction conditions were found to be as follows: the materials ratio n(ACOF)∶n(NH 2 OH•HCl)∶n(CH 3 ONa) was 1∶2∶3, reaction temperature 30 ℃, and reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…The bond lengths of C1−N3 (1.379(3) Å) and N3−N4 (1.315(2) Å) and angle of N4‐N3‐C1 (115.98(16)°) in the nitramino group of the anion are in accordance with those of reported nitraminofurazan‐based salts . The bond length of C2−C3 (1.463(3) Å) is obviously stretched compared with the reported bis(dinitromethyl)difurazanyl ethers; this might be due to the exclusion of negative charges between the nitramino and dinitromethyl groups. In contrast with compounds that contain a near‐planar dinitromethyl anion group, the oxygen atoms on the two nitro groups of salt 1 were twisted out of the [N6, C3, N5] plane, and the plane defined by the nitro group that is closest to the nitramino moiety, [O6, N6, O7], has a larger torsion angle of −10.4°, which might be caused by the repulsive effect of the nearby O7 and N3 atoms.…”
Section: Resultssupporting
confidence: 81%
“…The bond lengths of C1−N3 (1.379(3) Å) and N3−N4 (1.315(2) Å) and angle of N4‐N3‐C1 (115.98(16)°) in the nitramino group of the anion are in accordance with those of reported nitraminofurazan‐based salts . The bond length of C2−C3 (1.463(3) Å) is obviously stretched compared with the reported bis(dinitromethyl)difurazanyl ethers; this might be due to the exclusion of negative charges between the nitramino and dinitromethyl groups. In contrast with compounds that contain a near‐planar dinitromethyl anion group, the oxygen atoms on the two nitro groups of salt 1 were twisted out of the [N6, C3, N5] plane, and the plane defined by the nitro group that is closest to the nitramino moiety, [O6, N6, O7], has a larger torsion angle of −10.4°, which might be caused by the repulsive effect of the nearby O7 and N3 atoms.…”
Section: Resultssupporting
confidence: 81%
“…Since there is no weaker repulsion between lone pair orbitals of O6 and N15 in the Back-to-Face conformer 2, its potential energy is slightly lower than that of Face-to-Back conformer 1 (see Figure 2). Figure 2 should be here M06-2X optimization found that there is no stable Face-to-Face minimum (the planar or the slightly tilted) on the H2BTF PES, which is different from the experimental geometry [8]. Similar optimization at the level of B3LYP/6-311+G(d,p) and MP2/6-311+G(d,p) leads to the same conclusion as the M06-2X optimization.…”
Section: Molecular Structure and Chemical Bondmentioning
confidence: 70%
“…The density of H2BTF in P212121 space group was previously reported to be 1.76 g/cm 3 [8]. However, other polymorphs could have existed, through rotation of the tetrazole rings relative to the furoxan ring, and therefore a more detailed theoretical study was performed in this work.…”
Section: Crystal Form and Densitymentioning
confidence: 90%
See 1 more Smart Citation
“…Compounds 1a [17] and 1c [18] were obtained as previously reported. All other solvents and reagents were obtained from commercial vendors and used as received.…”
Section: Methodsmentioning
confidence: 99%